A meta-heuristic optimization-based approach for 3D simplified parametric analysis of embedded soil-foundation systems undergoing coupled horizontal-rocking vibrations. (March 2023) - Chen, Shi-Shuenn; Shi, Jun-Yang; Doan, Minh-Tam
Abstract: This paper presents a novel modeling approach based on meta -heuristic optimization for constructing adaptive lumped-parameter models to approximate the dynamic response of a shallow foundation in layered soil considering coupled horizontal and rocking vibrations. The developed model is adaptive to complexities of impedance functions for different types of layered soil deposits. The optimal parameters of the proposed model are computed using three optimization algorithms, with the forensic-based investigation outperforming the others and being chosen as the best optimization strategy for numerical investigations. A parametric study of foundation characteristics and soil properties on frequency response curves, including magnification factors and phase angle, is performed to comprehensively verify the proposed model's appropriateness. The findings reveal that dynamic responses of the proposed simplified systems are perfectly consistent with those computed using existing impedances and worldwide-recognized software in both frequency and time domains. It shall be concluded that the proposed model is compatible with different soil profiles and more effective than existing models in approximating the unbounded behavior of layered soil. Furthermore, it offers great potential to implement the time-history analysis of interacting systems subjected to forced vibrations and seismic motions in commercial software based on the proposed model for engineering practice.